2003
DOI: 10.1002/ijc.11448
|View full text |Cite
|
Sign up to set email alerts
|

EGF +61 gene polymorphism and susceptibility to and prognostic markers in cutaneous malignant melanoma

Abstract: CMM is the most serious cutaneous malignancy and is increasing in frequency among most Caucasian populations, where the most important risk factor is exposure to UV light. Relatively little is known of the genetic factors that mediate susceptibility to and prognosis in sporadic CMM, although a number of genes have been implicated. A striking association between EGF polymorphism and Breslow thickness of invasive CMM has been reported. We have sought confirmation of this finding in an independent study of 159 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
6
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 15 publications
7
47
6
1
Order By: Relevance
“…In this study, the EGF 61A allele frequency (0.273) in control was close to that reported in the Chinese (0.297, 0.305), 14,24 Korean (0.284) 25 and Japanese populations (0.313, 0.304), 12,13 but was significantly lower than that in the Caucasians (higher than 0.500). 10,11,26,27 Therefore, we confirmed that EGF genotypes were significantly different between the East Asian and Caucasian populations. The ethnic heterogeneity in this polymorphism suggests the possibility that constitutive EGF expression may vary between different ethnic groups.…”
Section: Characteristics Of the Study Populationsupporting
confidence: 71%
“…In this study, the EGF 61A allele frequency (0.273) in control was close to that reported in the Chinese (0.297, 0.305), 14,24 Korean (0.284) 25 and Japanese populations (0.313, 0.304), 12,13 but was significantly lower than that in the Caucasians (higher than 0.500). 10,11,26,27 Therefore, we confirmed that EGF genotypes were significantly different between the East Asian and Caucasian populations. The ethnic heterogeneity in this polymorphism suggests the possibility that constitutive EGF expression may vary between different ethnic groups.…”
Section: Characteristics Of the Study Populationsupporting
confidence: 71%
“…Shahbazi reported that the 61*G/G genotype was significantly associated with Breslow thickness and the risk to develop a malignant melanoma, and melanocytes cultured from individuals homozygous for the 61*A allele produced significantly less EGF than cells derived from 61*G homozygous or heterozygous A/G individuals (Shahbazi et al, 2002). It was also demonstrated that the EGF 61* gene polymorphism played a role for the progression of malignant melanoma (McCarron et al, 2003). Recently, it has been reported that gastric cancer and glioma were related to EGF 61* gene polymorphism (Hamai et al, 2005;Costa et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…In vitro studies showed that G-carriers have an increased EGF production in both normal and tumoral cells. [11][12][13] This functional polymorphism has been associated with several malignancies, [11][12][13][14][15] including an earlier report from our group in PC. 16 Transforming growth factor-b 1 is a multifunctional regulatory polypeptide that controls many aspects of cellular function, such as cellular proliferation, differentiation, migration, apoptosis, adhesion, angiogenesis, immune surveillance and survival.…”
Section: Introductionmentioning
confidence: 67%
“…EGF þ 61G4A polymorphism has been the subject of investigation in case-control studies, involving other cancer types. [11][12][13][14][15][16] Recently, we have shown that this functional polymorphism was associated with increased risk for PC, being diagnosed with aggressive disease and worst response to ADT. 16 The TGFB1 þ 869T4C functional polymorphism is responsible for significantly higher TGF-b 1 circulating levels in C-carriers and in vitro transfection experiments showed that the signal peptide in C-carriers caused a 2.8-fold increase in the secretion of TGF-b 1 compared with T-carriers.…”
Section: Discussionmentioning
confidence: 99%